Single-component silane modified polyether grouting material as well as preparation method and application thereof

By using a single-component silane-modified polyether grouting material, the wet curing mechanism is used to form a compact elastomer, the brittleness problem of traditional polyurethane grouting materials is solved, the permanent water blocking effect of the building is achieved, and the production efficiency is improved, making it suitable for large-scale industrial production.

CN119638940APending Publication Date: 2025-03-18SHANGHAI DONGDA CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411761513.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing polyurethane grouting materials have brittle problems in their applications, and they are difficult to withstand the slight displacement and deformation of buildings due to temperature changes, thermal expansion and contraction, and foundation vibration, resulting in a reduced waterproofing effect and an increase in building maintenance costs.

Method used

A single-component silane-modified polyether grouting material is used, which consists of polyether polyols, isocyanates, plasticizers, fillers, pigments, wetting and dispersants, catalysts, secondary aminosilane blocking agents, water absorbents and silane coupling agents. A compact elastomer is formed through a moisture curing mechanism, with good mechanical strength and elastic elongation.

Benefits of technology

The compact elastomer formed after the material is cured can effectively resist the displacement and deformation of the building due to temperature changes and foundation vibration, achieve permanent water blocking effect, make up for the insufficient brittleness of traditional polyurethane grouting materials, and at the same time improve production efficiency, which is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005167799550000101
    Figure BDA0005167799550000101
Patent Text Reader

Abstract

The invention belongs to the technical field of silane modified polyether materials and preparation thereof, and particularly relates to a single-component silane modified polyether grouting material as well as a preparation method and application thereof. The single-component silane modified polyether grouting material provided by the invention is prepared from the following raw materials in parts by weight: 20-30 parts of polyether polyol; 0.9 to 1.5 parts of isocyanate; 25 to 30 parts of a plasticizer; 32.4 to 44 parts of a filling material; 0.1 to 0.2 part of pigment; 0.3 to 0.8 part of a wetting dispersant; 0.1 to 0.2 part of a catalyst; 1.3 to 2.5 parts of a secondary amino silane end-capping agent; 1-2 parts of a water absorbent; and 1-2 parts of a silane coupling agent. The single-component silane modified polyether grouting material provided by the invention can form a dense elastomer after being cured, has better mechanical strength and elastic elongation, can bear infinitesimal displacement and deformation of a building caused by factors such as temperature change, thermal expansion and cold contraction, foundation vibration and the like, and has a permanent water plugging effect. The invention also provides a preparation method and application thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silane-modified polyether materials and preparation thereof, and in particular relates to a single-component silane-modified polyether grouting material and a preparation method and application thereof. Background Art

[0002] At present, in the construction industry, waterproofing has always been one of the key factors affecting building quality and living comfort. With the acceleration of urbanization and the improvement of people's requirements for living environment, the importance of building waterproofing technology has become increasingly prominent. At present, polyurethane grouting materials widely used in the market, as one of the main means to solve the problem of water seepage in building cracks, are mainly divided into two categories: water-based and oil-based. This type of material is injected into the cracks of the building and uses its properties after curing to form a water-blocking barrier, which can effectively prevent water penetration in a short period of time, and plays a positive role in improving the waterproof performance of the building.

[0003] However, polyurethane grouting materials have obvious limitations in their applications. Cured polyurethane materials often show brittle characteristics, which means that they are difficult to withstand the slight displacement and deformation of buildings caused by temperature changes, thermal expansion and contraction, and foundation vibration. Over time, these brittle materials are prone to cracking under stress, resulting in a significant reduction in the waterproof effect and even causing leakage problems again, thereby increasing the cost and difficulty of building maintenance.

[0004] To solve the above problems, the industry has tried to use silane-modified polyether as raw material to develop new coatings or adhesive products in order to improve the flexibility and durability of waterproof materials. The traditional method of producing such products relies on a planetary mixer, which adds silane-modified polyether, plasticizer, solid filler and related additives to the mixer in proportion and mixes them evenly to finally obtain the desired product. Although this method meets production needs to a certain extent, its production capacity bottleneck cannot be ignored.

[0005] Specifically, the design production volume of the mainstream planetary mixers on the market is usually 1 cubic meter, which means that the single batch production volume is limited and can only produce about 1 ton of products. This small-scale production method not only limits production efficiency and increases production costs, but also makes it difficult to meet the large demand for waterproof materials in large-scale projects. Therefore, developing a new production method that can not only improve the performance of waterproof materials but also significantly improve production efficiency has become a technical problem that needs to be solved in the field of building waterproofing. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a single-component silane-modified polyether grouting material, which can form a dense elastic body after curing, has good mechanical strength and elastic elongation, can resist thermal expansion and contraction and vibration displacement of buildings, and achieve a permanent water blocking effect. The present invention also provides a preparation method and specific applications thereof.

[0007] The one-component silane-modified polyether grouting material of the present invention is made of the following raw materials in parts by weight: polyether polyol: 20-30 parts; isocyanate: 0.9-1.5 parts; plasticizer: 25-30 parts; filler: 32.4-44 parts; pigment: 0.1-0.2 parts; wetting dispersant: 0.3-0.8 parts; catalyst: 0.1-0.2 parts; secondary aminosilane capping agent: 1.3-2.5 parts; water absorbent: 1-2 parts; silane coupling agent: 1-2 parts;

[0008] The polyether polyol is one or two PPG (polypropylene glycol) type polyethers with a functionality of 2 and a number average molecular weight of 8000 to 12000. Preferably, the two polyethers C280 and C2120 are produced by Shanghai Dongda Chemical Co., Ltd. The molecular weight of the polyether is large enough to ensure the mechanical properties and elongation of the material.

[0009] The secondary aminosilane end-capping agent is one of N-(n-butyl)-3-aminopropyltrimethoxysilane (1189) and bis(trimethoxysilylpropyl)amine (1124). The secondary aminosilane end-capping agent is a compound containing both secondary amino groups and siloxane groups in one molecule. The secondary amino groups react with isocyanate-terminated polyethers to obtain siloxane-terminated polyurethane macromolecules. The urea groups generated by the reaction of amino groups with isocyanate provide great mechanical strength for the material, while the polyethers as soft segments in the molecules provide good elongation for the material.

[0010] The isocyanate is one of toluene diisocyanate, diphenylmethane diisocyanate or isophorone diisocyanate, preferably TDI-80, MDI-50 or IPDI, all of which are purchased from Wanhua Chemical Group Co., Ltd. The isocyanate can react with the polyether to form a carbamate chemical bond to obtain a prepolymer macromolecule terminated with an NCO group. The carbamate bond can provide greater mechanical strength for the material.

[0011] The plasticizer is a phthalate plasticizer or a citrate plasticizer, preferably one of diisononyl phthalate (DINP), diisodecyl phthalate (DIDP), and tributyl citrate (TBC), which can improve the elongation of the material and reduce the viscosity of the finished product.

[0012] The filler is one or more combinations of heavy calcium carbonate, talcum powder or silicon micropowder, which can reduce material costs and improve the mechanical properties of the material.

[0013] The catalyst is a tin catalyst, including one or more of stannous octoate, dibutyltin dilaurate, and chelated tin.

[0014] The pigment is one of carbon black or titanium dioxide.

[0015] The wetting and dispersing agent is one of BYK-168, BYK-154 and BYK-1165, all of which are purchased from BYK Chemical Co., Ltd.

[0016] The water absorbent is one or both of vinyl trimethoxy silane (171) and vinyl triethoxy silane (151).

[0017] The silane coupling agent is one or more of 3-aminopropyltrimethoxysilane (KH-540), γ-aminopropyltriethoxysilane (KH-550), and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH-792).

[0018] The preparation method of the one-component silane-modified polyether grouting material comprises the following steps:

[0019] (1) adding the formulated amount of polyether polyol, plasticizer, wetting dispersant, filler and pigment into a reaction kettle, heating to 100-120° C., vacuum dehydrating to a water content of ≤0.03 wt.%, and cooling to 40-50° C.;

[0020] (2) Add isocyanate and catalyst, stir evenly, start heating to 60-70°C, and react for 3-5 hours;

[0021] (3) Cooling to 40-50°C, adding secondary aminosilane capping agent, and keeping the temperature for reaction for 2-4 hours;

[0022] (4) adding a water absorbent, a silane coupling agent, and a catalyst, stirring for 30 to 60 minutes, and performing a vacuum degassing treatment to obtain a single-component silane-modified polyether grouting material; the solid content of the obtained product is above 99%.

[0023] The catalyst described above was added in two portions.

[0024] Application of the one-component silane-modified polyether grouting material: directly grouting the one-component silane-modified polyether grouting material, or adding 3-5wt.% of water to the one-component silane-modified polyether grouting material and stirring it evenly before grouting.

[0025] The present invention provides a single-component silane-modified polyether grouting material, which adopts a wet curing mechanism. The siloxane groups at both ends of the macromolecule will produce a cross-linking effect after reacting with water molecules, so that the liquid material gradually solidifies and forms a network of macromolecular structures. In combination with the solid filler and plasticizer therein, the material has high mechanical strength and elongation, and does not foam on the surface and inside, showing dense elastomeric properties. This material with both strength and elasticity makes up for the shortcomings of brittle materials formed after the traditional polyurethane grouting material is cured, and can withstand the slight displacement and deformation of the building caused by factors such as temperature changes, thermal expansion and contraction, and foundation vibration, thereby achieving a permanent water blocking effect. At present, research reports on this field are relatively rare, so the present invention is expected to fill this gap.

[0026] Another object of the present invention is to provide a more advanced production method of silane-modified polyether grouting material. The traditional production method usually uses silane-modified polyether as raw material, and uses a planetary mixer to add and stir silane-modified polyether, plasticizer, solid filler and related additives. However, this method has a small production capacity. The production volume of the common planetary mixer on the market is 1 cubic meter, and a single batch can only produce about 1 ton of products. This is mainly due to the high viscosity of the silane-modified polyether material. The viscosity of conventional products is generally between 50000-100000 mPa·s, and the high stirring power of the planetary mixer is required to fully mix. This production method not only has low output, but also high energy consumption. In contrast, the production method provided by this patent is more advanced, and can directly produce finished silane-modified polyether grouting materials from polyether. This method uses a large reactor of 5-20 cubic meters for production, and the single batch production capacity can be increased by 5 to 20 times, significantly improving production efficiency. This is because the raw material used in this method is polyether, which has a low viscosity, generally 3000-8000mPa·s, which is more than ten times lower than the viscosity of the finished silane-modified polyether. Therefore, it can be easily added to a large reactor, and the energy consumption is much lower than that of a planetary mixer. In addition, this production method avoids the secondary production step of first producing silane-modified polyether and then processing it into silane-modified polyether grouting material, further improving production efficiency.

[0027] The one-component silane-modified polyether grouting material of the present invention can be used alone. In order to accelerate the curing time of the material, 3-5 wt.% of water (this mass percentage is 3-5 wt.% of the one-component silane-modified polyether grouting material) can be added thereto and stirred evenly before use. The one-component silane-modified polyether grouting material of the present invention relies on reaction with water to cure, and the curing speed is relatively fast. Usually, the finished product is placed at room temperature, and the surface drying phenomenon of the liquid finished product can appear in 30-60 minutes. Therefore, when using it, it is necessary to pay attention to that the finished product should be used up within 10 minutes after contact with air or water.

[0028] For larger gaps such as deformation joints, joints, expansion joints, settlement joints, etc. between buildings, the product can be poured directly into the gaps; for smaller gaps in buildings, a high-pressure grouting machine can also be used to inject the product into the gaps, and the material can have a water-blocking effect after solidification.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The silane-modified polyether grouting material of the present invention is a single-component product. Compared with a two-component product, it is convenient and quick to use, thereby improving construction efficiency.

[0031] (2) The silane-modified polyether grouting material of the present invention is a dense elastomeric material with high mechanical strength after curing during use, which can completely block water in one go, thus making up for the deficiency that the traditional polyurethane grouting material is a brittle material after curing and can only block water temporarily.

[0032] (3) The single-component silane-modified polyether grouting material prepared by the method of the present invention has no solvent addition, high solid content, is relatively environmentally friendly, and the batch production volume is 5-20 times that of the traditional production method, which is suitable for large-scale industrial production. DETAILED DESCRIPTION

[0033] The present invention will be further described below with reference to the embodiments.

[0034] The raw materials used in the examples and comparative examples are all conventional commercially available raw materials unless otherwise specified. The weight parts described below are all based on the same unit of mass. The weight parts of the catalyst and in the following steps are the weight parts of the raw material components.

[0035] The specific preparation process of the polyether polyol C220 described below is: in a nitrogen environment, 1 part by weight of propylene glycol is added as a raw material to a stirred reactor, 0.02 parts by weight of a DMC catalyst is used, 33 parts by weight of propylene oxide is gradually added thereto, and the reaction is carried out at 130°C, so that the propylene oxide is gradually ring-opened and connected to the propylene glycol, thereby obtaining polyether polyol C220, whose functionality is 2 and the number average molecular weight is 2000.

[0036] The specific preparation process of the polyether polyol C280 described below is: in a nitrogen environment, 1 part by weight of propylene glycol is added as a raw material to a stirred reactor, 0.02 parts by weight of a DMC catalyst is used, 136 parts by weight of propylene oxide is gradually added thereto, and the reaction is carried out at 130°C, so that the propylene oxide is gradually ring-opened and connected to the propylene glycol, thereby obtaining polyether polyol C280, whose functionality is 2 and the number average molecular weight is 8000.

[0037] The specific preparation process of the polyether polyol C2120 described below is: in a nitrogen environment, add 1 part by weight of propylene glycol as a raw material into a stirred reactor, use 0.02 parts by weight of DMC catalyst, gradually add 205 parts by weight of propylene oxide thereto, and react at 130°C to allow the propylene oxide to gradually open its ring and then connect to the propylene glycol, thereby obtaining polyether polyol C2120, which has a functionality of 2 and a number average molecular weight of 12,000.

[0038] Example 1

[0039] The one-component silane-modified polyether grouting material is made of the following raw materials in parts by weight:

[0040] Polyether polyol: C280: 25 parts;

[0041] Isocyanate: TDI-80: 1.1 parts;

[0042] Plasticizer: DINP: 25 parts;

[0043] Filler: Heavy calcium carbonate: 44 parts;

[0044] Pigment: Carbon black: 0.2 parts;

[0045] Wetting and dispersing agent: BYK-168: 0.5 parts;

[0046] Catalyst: stannous octoate: 0.2 parts;

[0047] Secondary aminosilane capping agent: 1189: 1.5 parts;

[0048] Water absorbent: 171: 1.5 parts;

[0049] Silane coupling agent: KH-540: 1 part.

[0050] The preparation method of the one-component silane-modified polyether grouting material comprises the following steps:

[0051] (1) Add the above-mentioned polyether polyol C280, plasticizer DINP, filler heavy calcium carbonate, pigment carbon black, and wetting dispersant BYK-168 into a reactor, heat it to 110° C., and use a vacuum pump to vacuum dehydrate the materials in the reactor for 3 hours. The moisture content is detected to be 0.01%, and then cool it to 40° C.;

[0052] (2) adding isocyanate TDI-80 and 0.05 parts of stannous octoate catalyst, stirring until the temperature is stable, and then heating to 60° C. to react for 5 hours;

[0053] (3) Cooling to 40°C, adding secondary aminosilane capping agent 1189, and reacting at 40°C for 4 hours;

[0054] (4) Add water absorbent 171, silane coupling agent KH-540, and 0.15 parts of catalyst stannous octoate, stir for 30 minutes and vacuum degas to obtain a finished product.

[0055] Application of the one-component silane-modified polyether grouting material: directly pour the finished product prepared above into the gaps of a building, and wait for the material to solidify to achieve the water blocking effect. The pouring operation time is 5 minutes.

[0056] Example 2

[0057] The one-component silane-modified polyether grouting material is composed of the following raw materials in parts by weight:

[0058] Polyether polyol: C2120: 20 parts;

[0059] Isocyanate: MDI-50: 0.9 parts;

[0060] Plasticizer: DIDP: 30 parts;

[0061] Filler: talc: 43.7 parts;

[0062] Pigment: Titanium dioxide: 0.2 parts;

[0063] Wetting and dispersing agent: BYK-154: 0.8 parts;

[0064] Catalyst: dibutyltin dilaurate: 0.1 parts;

[0065] Secondary aminosilane capping agent: 1124: 1.3 parts;

[0066] Water absorbent: 151: 1 part;

[0067] Silane coupling agent: KH-550: 2 parts.

[0068] The preparation method of the one-component silane-modified polyether grouting material comprises the following steps:

[0069] (1) Add the above-mentioned polyether polyol C2120, plasticizer DIDP, filler talcum powder, pigment titanium dioxide, and wetting dispersant BYK-154 into a reactor, heat it to 120° C., and use a vacuum pump to vacuum dehydrate the materials in the reactor for 2 hours. The moisture content is detected to be 0.02%, and then cool it to 50° C.;

[0070] (2) adding isocyanate MDI-50 and 0.05 parts of dibutyltin dilaurate as a catalyst, stirring until the temperature is stable, and then heating to 70° C. to react for 3 hours;

[0071] (3) Cooling to 50°C, adding secondary aminosilane capping agent 1124, and reacting at 50°C for 2h;

[0072] (4) Add water absorbent 151, silane coupling agent KH-550, and 0.05 parts of dibutyltin dilaurate as a catalyst, stir for 60 minutes and vacuum degas to obtain a finished product.

[0073] Application of the one-component silane-modified polyether grouting material: 4 wt.% of the finished product is mixed with water and poured into the gaps of the building, and the water blocking effect is achieved after the material solidifies. The operation time from the start of adding water to the end of pouring is 10 minutes.

[0074] Example 3

[0075] The one-component silane-modified polyether grouting material is composed of the following raw materials in parts by weight:

[0076] Mixed polyether polyol: C280: 20 parts and C2120: 10 parts;

[0077] Isocyanate: IPDI: 1.5 parts;

[0078] Plasticizer: TBC: 30 parts;

[0079] Filler: Silica powder: 32.4 parts;

[0080] Pigment: Carbon black: 0.1 part;

[0081] Wetting and dispersing agent: BYK-1165: 0.3 parts;

[0082] Catalyst: dibutyltin dilaurate: 0.2 parts;

[0083] Secondary aminosilane capping agent: 1124: 2.5 parts;

[0084] Water absorbent: 171: 2 parts;

[0085] Silane coupling agent: KH-792: 1 part.

[0086] The preparation method of the one-component silane-modified polyether grouting material comprises the following steps:

[0087] (1) Add the mixed polyether polyols C280 and C2120, plasticizer TBC, filler silica powder, pigment carbon black, and wetting dispersant BYK-1165 in the reaction kettle, heat to 100° C., and use a vacuum pump to vacuum dehydrate the materials in the reaction kettle for 3 hours. The moisture content is detected to be 0.02%, and then cool to 50° C.;

[0088] (2) adding isocyanate IPDI and 0.05 parts of catalyst dibutyltin dilaurate, stirring until the temperature is stable, and then heating to 65° C. to react for 5 hours;

[0089] (3) Cooling to 45°C, adding secondary aminosilane capping agent 1124, and reacting at 50°C for 3h;

[0090] (4) Add water absorbent 171, silane coupling agent KH-792, and 0.15 parts of dibutyltin dilaurate as a catalyst, stir for 60 minutes, and evacuate and degas to obtain a finished product.

[0091] Application of the one-component silane-modified polyether grouting material: the finished product is injected into the gap of the building with a high-pressure grouting machine, and the water blocking effect can be achieved after the material solidifies. The operation time from the beginning of injection to the end is 10 minutes.

[0092] Comparative Example 1

[0093] The one-component silane-modified polyether grouting material is composed of the following raw materials in parts by weight:

[0094] Polyether polyol: C280: 15 parts;

[0095] Isocyanate: TDI-80: 0.7 parts;

[0096] Plasticizer: DINP: 32 parts;

[0097] Filler: Heavy calcium carbonate: 47.9 parts;

[0098] Pigment: Carbon black: 0.2 parts;

[0099] Wetting and dispersing agent: BYK-168: 0.5 parts;

[0100] Catalyst: stannous octoate: 0.2 parts;

[0101] Secondary aminosilane capping agent: 1189: 1 part;

[0102] Water absorbent: 171: 1.5 parts;

[0103] Silane coupling agent: KH-540: 1 part.

[0104] The preparation method of the single-component silane-modified polyether grouting material has the same steps as Example 1.

[0105] Comparative Example 2

[0106] The one-component silane-modified polyether grouting material is composed of the following raw materials in parts by weight:

[0107] Polyether polyol: C2120: 20 parts;

[0108] Isocyanate: MDI-50: 0.9 parts;

[0109] Plasticizer: DIDP: 30 parts;

[0110] Filler: talc: 46.5 parts;

[0111] Pigment: Titanium dioxide: 0.2 parts;

[0112] Catalyst: dibutyltin dilaurate: 0.1 parts;

[0113] Secondary aminosilane capping agent: 1124: 1.3 parts;

[0114] Water absorbent: 151: 1 part.

[0115] The preparation method of the single-component silane-modified polyether grouting material has the same steps as Example 2.

[0116] Comparative Example 3

[0117] The one-component silane-modified polyether grouting material is composed of the following raw materials in parts by weight:

[0118] Mixed polyether polyol: C280: 20 parts and C2120: 10 parts;

[0119] Isocyanate: IPDI: 1.5 parts;

[0120] Plasticizer: TBC: 25 parts;

[0121] Filler: Silica powder: 32.4 parts;

[0122] Pigment: Carbon black: 0.1 part;

[0123] Wetting and dispersing agent: BYK-1165: 0.3 parts;

[0124] Catalyst: dibutyltin dilaurate: 0.2 parts;

[0125] Secondary aminosilane capping agent: 1124: 2.5 parts;

[0126] Water absorbent: 171: 2 parts;

[0127] Silane coupling agent: KH-792: 1 part;

[0128] Solvent oil: Tetramethylbenzene: 5 parts.

[0129] The preparation method of the one-component silane-modified polyether grouting material has the same steps as Example 2, the only difference being that 5 parts of solvent oil are added to the reaction kettle before the degassing step.

[0130] Comparative Example 4

[0131] The one-component silane-modified polyether grouting material is composed of the following raw materials in parts by weight:

[0132] Polyether polyol: C220: 25 parts;

[0133] Isocyanate: TDI-80: 4.4 parts;

[0134] Plasticizer: DINP: 25 parts;

[0135] Filler: Heavy calcium carbonate: 36.2 parts;

[0136] Pigment: Carbon black: 0.2 parts;

[0137] Wetting and dispersing agent: BYK-168: 0.5 parts;

[0138] Catalyst: stannous octoate: 0.2 parts;

[0139] Secondary aminosilane capping agent: 1189: 6 parts;

[0140] Water absorbent: 171: 1.5 parts;

[0141] Silane coupling agent: KH-540: 1 part.

[0142] The preparation method of the single-component silane-modified polyether grouting material has the same steps as Example 1.

[0143] Comparative Example 5

[0144] The one-component silane-modified polyether grouting material is composed of the following raw materials in parts by weight:

[0145] Polyether polyol: C2120: 20 parts;

[0146] Isocyanate: MDI-50: 0.9 parts;

[0147] Plasticizer: DIDP: 30 parts;

[0148] Filler: talc: 43.7 parts;

[0149] Pigment: Titanium dioxide: 0.2 parts;

[0150] Wetting and dispersing agent: BYK-154: 0.8 parts;

[0151] Catalyst: dibutyltin dilaurate: 0.1 parts;

[0152] Silane coupling agent: KH-540: 1.3 parts;

[0153] Water absorbent: 151: 1 part;

[0154] Silane coupling agent: KH-550: 2 parts.

[0155] The preparation method of the single-component silane-modified polyether grouting material has the same steps as Example 2.

[0156] The silane-modified polyether grouting materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to performance tests. The test method was based on T / CECS10301-2023. The test results are shown in Table 1:

[0157] Table 1 Performance test results

[0158]

[0159] It can be seen from Table 1 that the single-component silane-modified polyether grouting materials prepared in Examples 1 to 3 have better performance. Compared with Example 1, Comparative Example 1 uses a lower proportion of polyether, while the content of plasticizer and powder increases accordingly, resulting in a lower content of resin synthesized inside the finished product, and a decrease in the mechanical properties of the material such as tensile strength and bonding strength; Compared with Example 2, Comparative Example 2 cancels the addition of dispersant and silane coupling agent. The dispersant can make the powder evenly distributed in the liquid, and the silane coupling agent can increase the cross-linking points in the resin curing, both of which can play a role in improving the mechanical properties. After cancellation, the tensile strength and bonding strength are significantly reduced; Compared with Example 3, Comparative Example 3 reduces part of the plasticizer and replaces it with solvent oil. There is no obvious change in tensile strength and bonding strength, but the solid content decreases significantly. The addition of solvent oil will produce a Compared with Example 1, Comparative Example 4 uses C220 polyether, and the ratio of isocyanate and secondary aminosilane reacted therewith is also increased accordingly, and the powder content is decreased accordingly. Because the molecular weight of the polyether used is small, the elongation at break of the material after curing is short, and the brittleness is relatively large. When it is poured into the cracks of the building, it is not enough to maintain the vibration displacement of the building, and there is a risk of cracking, and the water plugging effect is limited; Compared with Example 2, Comparative Example 5 replaces the secondary aminosilane capping agent 1124 with the silane coupling agent KH-540, which is a primary aminosilane capping agent. The reaction of the primary amino group with the NCO group is very fast. After addition, gel and agglomeration are generated in the reactor due to the excessive local reaction, and the experimental synthesis fails.

Claims

1. A one-component silane-modified polyether grouting material, characterized in that: The invention is prepared from the following raw materials in parts by weight: polyether polyol: 20-30 parts; isocyanate: 0.9-1.5 parts; plasticizer: 25-30 parts; filler: 32.4-44 parts; pigment: 0.1-0.2 parts; wetting dispersant: 0.3-0.8 parts; catalyst: 0.1-0.2 parts; secondary aminosilane end-capping agent: 1.3-2.5 parts; water absorbent: 1-2 parts; silane coupling agent: 1-2 parts; The polyether polyol is a polypropylene glycol type polyether polyol with a functionality of 2 and a number average molecular weight of 8000-12000.

2. The one-component silane-modified polyether grouting material according to claim 1, characterized in that: The secondary aminosilane end-capping agent is one of N-(n-butyl)-3-aminopropyltrimethoxysilane and bis(trimethoxysilylpropyl)amine.

3. The one-component silane-modified polyether grouting material according to claim 1, characterized in that: The isocyanate is one of toluene diisocyanate, diphenylmethane diisocyanate or isophorone diisocyanate.

4. The one-component silane-modified polyether grouting material according to claim 1, characterized in that: The plasticizer is a phthalate plasticizer or a citrate plasticizer.

5. The one-component silane-modified polyether grouting material according to claim 1, characterized in that: The filler is one or more of heavy calcium carbonate, talcum powder or silicon powder; and the catalyst is a tin catalyst.

6. The one-component silane-modified polyether grouting material according to claim 1, characterized in that: The wetting and dispersing agent is one of BYK-168, BYK-154 and BYK-1165.

7. The one-component silane-modified polyether grouting material according to claim 1, characterized in that: The water absorbent is one or both of vinyl trimethoxy silane and vinyl triethoxy silane.

8. The one-component silane-modified polyether grouting material according to claim 1, characterized in that: The silane coupling agent is one or more of 3-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

9. A method for preparing the one-component silane-modified polyether grouting material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) adding the formulated amount of polyether polyol, plasticizer, wetting dispersant, filler and pigment into a reaction kettle, heating to 100-120° C., vacuum dehydrating to a water content of ≤0.03 wt.%, and cooling to 40-50° C.; (2) Add isocyanate and catalyst, stir evenly, start heating to 60-70°C, and react for 3-5 hours; (3) Cooling to 40-50°C, adding secondary aminosilane capping agent, and keeping the temperature for reaction for 2-4 hours; (4) adding a water absorbent, a silane coupling agent, and a catalyst, stirring for 30 to 60 minutes, and performing a vacuum degassing treatment to obtain a single-component silane-modified polyether grouting material; The catalyst described above was added in two portions.

10. An application of the one-component silane-modified polyether grouting material according to any one of claims 1 to 8, characterized in that: The one-component silane-modified polyether grouting material is directly used for grouting, or 3-5 wt.% of water is added to the one-component silane-modified polyether grouting material and stirred evenly before grouting.